XSLT 2.0 and XPath 2.0 Programmer's Reference (Programmer to Programmer) - Kay, Michael (Wrox, 2011)
This book is primarily a practical reference book for professional XSLT developers. It assumes no previous knowledge of the language, and many developers have used it as their first introduction to XSLT; however, it is not structured as a tutorial, and there are other books on XSLT that provide a gentler approach for beginners.